PROCESS MODELING AND SCENARIO SIMULATION IN CONSTRUCTION USING ENTERPRISE DYNAMICS SIMULATION SOFTWARE (Advances in Civil and Architectural Engineering, 2021)
Modeling and simulation of organizational processes are established methodologies and tools in most industries. In civil engineering, however, this is not the case. One of the reasons for this is the lack of special tools, specifically computer programs used primarily for modeling and simulating characteristic processes of construction. In this paper the authors look for analogies between processes typical for construction and those in other industries in which Enterprise Dynamics software has been successfully applied. In order to perform a valid software analysis, the authors tested this software in a case study that represents universal problems at construction sites: queuing and sequencing. In this study, authors modeled and simulated the production, transport, and laying of a hot asphalt mixture. Results show that this software is suitable for modeling and scenario simulation in this case and that the software shows promise for other uses in the construction industry.